2018
DOI: 10.1016/j.teln.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Partners in Learning: A Collaborative Model to Increase the Number of Baccalaureate-Prepared Nurses

Abstract: One bachelor of science in nursing (BSN)-granting institution sought to break down the barriers that many registered nurses encounter by forming partnerships with community colleges in the state to improve access and create as seamless a transition as possible from associate degree in nursing (ADN) to BSN. The following describes the current model used by 1 school, which would not be possible without the support and dedication of the community college partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…81 Previous studies have found that healthcare workers who interact one-on-one with elderly individuals have more negative stereotypes than workers in other sectors. [82][83][84][85] Research has reported that nurses and other healthcare workers tend to provide inadequate care or treatment for elderly individuals relative to youth, 61,86 and that they provide inadequate care because they attribute the physiological problems elderly individuals face to the incidental consequences of aging. 86 Some previous research exhibits similarities to our study while others differ.…”
Section: Discussionmentioning
confidence: 99%
“…81 Previous studies have found that healthcare workers who interact one-on-one with elderly individuals have more negative stereotypes than workers in other sectors. [82][83][84][85] Research has reported that nurses and other healthcare workers tend to provide inadequate care or treatment for elderly individuals relative to youth, 61,86 and that they provide inadequate care because they attribute the physiological problems elderly individuals face to the incidental consequences of aging. 86 Some previous research exhibits similarities to our study while others differ.…”
Section: Discussionmentioning
confidence: 99%